Flipping the Class: A New Media Pedagogy. (June 2016) - Arduser, Lora
Business communication evolves and adapts to suit the times, and today's workplace documents are increasingly multimodal. Therefore, business and professional communication specialists need to adapt to a new media workplace ecology—one that requires proficiencies with technologies such as video production, digital animation, and sound. Business and professional writing teachers, in turn, need to adopt teaching methods that include working with evolving technologies and be willing to teach multimodal skills to students. In this article I offer a case study of a flipped learning pedagogy to teach multimodal skills in the professional writing classroom.